Implementasi Kebijakan Rencana Penanggulangan Kemiskinan Daerah (RPKD) 2021-2026 di Kabupaten Kotawaringin Timur - Ramadani, Muhammad Pazri; Firdaus, Mohamad (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the implementation of the Regional Poverty Alleviation Plan (RPKD) 2021-2026 in East Kotawaringin Regency. A descriptive qualitative approach was used, employing interviews with informants from local government agencies, community leaders, and program beneficiaries. The data analysis applied Grindle’s policy implementation model, which includes five aspects: interest affected, resources committed, benefit distributed, degree of change, and decision-making location. The findings indicate that the policy implementation involves cross-sector actors coordinated by the Regional Poverty Alleviation Coordination Team (TKPKD). However, challenges remain in data synchronization, the accuracy of aid targeting, and limited community participation. The data system has shifted to the more integrative Regsosek system, although community economic empowerment efforts are still suboptimal. This study recommends strengthening coordination, ensuring data transparency, and enhancing the capacity of village officials in designing poverty alleviation programs based on local needs.